PSYCHOLOGICAL FEATURES OF INTERNET ADDICTION IN ADOLESCENT CHILDREN - Mushkevych, Myroslava (Personality and environmental issues, 2025)
Purpose of the study. The scientific research is devoted to the problem of adolescents’ Internet addiction to gadgets. Methodology. At various stages of the study, the following methods and technologies were used: interactive conversation, questionnaires (“To determine Internet addiction”), and testing (“Assessment of the development of volitional qualities,” “Study of volitional self-regulation,” “Diagnosis of achievement motivation”).Scientific novelty. It was found that Internet addiction may foster certain types of behavior in adolescents, the main ones being: a passion for virtual communication and online acquaintances; ignoring events around them; poor adaptation to real life; presence of certain physiological signs (general fatigue, reluctance to be active, weakness, aggressiveness, etc.), and informational overload. Conclusions. The study found that most modern parents allow their children to use gadgets without time limits, justifying this by the belief that it enhances development. At the same time, parents acknowledged the dangerous substitution of real personal life with virtual reality. It has been proven that children who spend excessive time in virtual information environments interact poorly with the real world, “drop out” of it, and experience social communication difficulties. A tendency among Internet-addicted adolescents to violate social norms and rules was identified, as well as a link between Internet addiction and the propensity for lying. A negative correlation was established between the level of computer addiction and the strength of will, which is typical for all forms of addictive behavior. A reverse relationship was also noted between the stage of computer addiction and the motivation level related to social significance. A negative correlation was found between the stages of computer addiction development and self-esteem in the areas of “appearance” and “self-confidence.” Decreased motivation is noted due to satisfying self-realization and self-expression needs in the virtual world. The article describes the social immaturity and infantilism of gadget addicts and highlights emotional-volitional sphere disorders and weakened volitional attitudes, which impair decision-making abilities and lead to a loss of behavioral control.